Potensi Wisata Pulau Sepandan di Taman Nasional Danau Sentarum Kabupaten Kapuas Hulu Kalimantan Barat - Utami, Weni Dewi; Abuyahman, Ridho Fajar; Sahrul, Sahrul (International Journal Labs, 2025)
Sentarum Lake National Park (SLNP) is a conservation area with unique natural and tourism potential. It is located in Kapuas Hulu Regency, West Kalimantan, specifically in Sepandan Village. The designation of Sentarum Lake National Park as a Ramsar Site in 1994 by the Ramsar Convention affirmed its status as an international wetland with high biodiversity, one of the world's rare biodiversity lakes that needs to be preserved globally. Once of a well-known island and sought-after tourist destination within the SLNP is Sepandan Island. Its natural resources, expansive and beautiful lake views, and conservation and cultural values make it a promising tourist destination. However, this significant potential is not fully supported by adequate infrastructure and other supporting tourism facilities. This study aims to explore and identify the tourism potential of Sepandan Island. The purpose of this study is to serve as a reference for tourism development in the SLNP, particularly Sepandan Island as a Transit Center. The research method was designed using a qualitative descriptive approach, which is guided by the principles of regional design that emphasizes the aspects of the Waterfront area and 3A Tourism (Attraction, Accessibility, and Amenity). The results of the study indicate that Sepandan Island has enormous tourism potential, including: 1) Natural Tourism (view of the beautiful expanse of the lake, sunrise and sunset views, as well as the wealth of other natural resources); 2) Cultural Tourism (local wisdom) in the form of the Sentarum Lake Festival which is an annual event and is also attended by invited guests from abroad; 3) Fostered Tourism, with the availability of accommodation facilities, tracking paths to the hilly areas, outbound areas and shelters as spots to enjoy the panorama from the top of the hill; 4) Global Conservation Value as a world wetland site that carries out ecological functions that need to be preserved; and 5) Endemic Biodiversity in the form of unique flora and fauna that are very well known such as Arwana Fish, Black Orchids and so on.